Morphological Shortening in Mobile Legend Video Game - Jannah, Salwa Raudhatul; Tawami, Tatan (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2024)
This study aims to classify the morphological types of shortening and explain their meaning. in Mobile Legends players within online community forums. The research methodology used qualitative methods and the data collected from Facebook Groups Mobile Legend: Bang Bang Official. This research used Schendl (2001) theories about five types of morphological shortening words, they are acronym, clipping, blends, contraction, and shortening. The research reveals that shortening serves multiple purposes in the gaming environment. They are primarily used to accelerate communication, thereby enhancing the efficiency of message delivery. Additionally, shortening creates a sense of belonging among players by fostering a shared linguistic culture. This study provides valuable insights into the dynamics of language within the online gaming context and explores how these shortening influence interactions among players. By understanding the role of morphological shortening, the research sheds light on how they enhance communication efficiency and build community cohesion in gaming environments. Keywords: Morphological Shortening, Game, Mobile Legends, Online Community